Punica granatumL. (Pomegranate): A Potential Anti-microbial Agent - Doostkam, Aida; Iravani, Kamyar; Bassiri-Jahromi, Shahindokht (Anti-Infective Agents, 2020)
Polyphenols have received high attention due to their biological functions. Pomegranate (Punica granatum L.) is a rich source of polyphenols such as tannin, ellagitannin, flavonoids and other phenolic acids. The potential therapeutic uses of pomegranate appear to be wide diversity. Pomegranate contains strong antioxidant activity, and antimicrobial properties, with potential health interests. This review has been performed on a method of systematic narrative review on the antimicrobial potency of different parts of pomegranate. A search was performed in PubMed, Web of Science, Science Direct, Scopus and Google Scholar from 1986 to 2018 to obtain related studies. The aim of this review present an overview of the aspect and advantages of Punica granatum L. and summarize the present data on the pomegranate anti-microbial activity in in-vitro and in-vivo tests, animal trial systems and human clinical trials. Also, this review discussed the pomegranate extracts activities and their future application. The findings of this review support that the pomegranate might be possible to use in the control and potential therapeutics of some microbial infections. This review highlights the new researches on the anti-microbial activities of pomegranate.
Keywords: antimicrobial